Sodium cromoglycate in nocturnal asthma. Issue 1 (January 1986) - Morgan, A D; Connaughton, J J; Catterall, J R; Shapiro, C M; Douglas, N J; Flenley, D C
Abstract : To investigate whether mast cell degranulation was important in producing nocturnal asthma, the effect of a single high dose of nebulised sodium cromoglycate on overnight bronchoconstriction, oxygen saturation, and breathing patterns in eight patients with nocturnal wheeze was examined. The study took the form of a double blind placebo controlled crossover comparison. Treatment with cromoglycate did not reduce the overnight fall in FEV1 or FVC, although it was associated with improved nocturnal oxygenation. This study suggests that mast cell degranulation may not be important in the pathogenesis of nocturnal asthma.